Pre-trip information and route-choice decisions with stochastic travel conditions: Experiment - Rapoport, Amnon; Gisches, Eyran J.; Daniel, Terry; Lindsey, Robin (Transportation research. Part B: methodological, 2014)
•In theory, providing information about travel conditions can increase travel costs.•We test the theory using laboratory experiments for a two-route congested network.•Subjects are given pre-trip information about travel conditions on each route.•We find that providing information increases costs as predicted.•Payoffs of individual subjects decrease with the frequency that they change route. This paper studies the effects of pre-trip information on route-choice decisions when travel conditions on two alternative congestible routes vary unpredictably. It presents and discusses an experiment designed to test a model recently proposed in a companion paper by Lindsey et al. (2013). That model predicts that if free-flow costs on the two routes are unequal, travel cost functions are convex, and capacities are positively and perfectly correlated, then in equilibrium, paradoxically, total expected travel costs increase with the provision of pre-trip information about travel conditions on each route. By contrast, when capacities vary independently, total expected travel costs are predicted to decrease with pre-trip information. We reformulate the model for finite populations, and then test and find support for its predictions in an experiment where under different capacity scenarios, and with and without pre-trip information, subjects are asked to choose routes with payoff contingent on their performance.